Microbiological Effect of Essential Oils in Combination with Subgingival Ultrasonic Instrumentation and Mouth Rinsing in Chronic Periodontitis Patients - Toshiya Morozumi; Takehiko Kubota; Daisuke Abe; Taro Shimizu; Kaname Nohno; Hiromasa Yoshie (International Journal of Dentistry, 2013)
Thirty chronic periodontitis patients were randomly assigned to 3 groups: control, saline, and essential oil-containing antiseptic (EO). Subgingival plaque was collected from a total of 90 pockets across all subjects. Subsequently, subgingival ultrasonic instrumentation (SUI) was performed by using EO or saline as the irrigation agent. After continuous mouth rinsing at home with EO or saline for 7 days, subgingival plaques were sampled again. Periodontopathic bacteria were quantified using the modified Invader PLUS assay. The total bacterial count in shallow pockets (probing pocket depth (PPD) = 4-5 mm) was significantly reduced in both saline (P<0.05) and EO groups (P<0.01). The total bacterial count (P<0.05) and Porphyromonas gingivalis (P<0.01) and Tannerella forsythia (P<0.05) count in deep pockets (PPD ≥6 mm) were significantly reduced only in the EO group. In comparisons of the change ratio relative to baseline value of total bacteria counts across categories, both the saline and EO groups for PPD 4-5 mm and the EO group for PPD 6 mm showed a significantly low ratio (P<0.05). The adjunctive use of EO may be effective in reducing subgingival bacterial counts in both shallow and deep pockets. This trial is registered with UMIN Clinical Trials Registry UMIN000007484.